The distribution, identity and virus vector potential of Xiphinema Spp. in the Western Cape Province - Malan, Antoinette P. (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. Agric.) -- University of Stellenbosch, 1995.